School Buildings in Mediterranean Antiquity: Notes on the Provenance of the Infancy Gospel of Thomas. (March 2021) - Bissell, Jonah
The provenance of the Infancy Gospel of Thomas (IGT) remains an open question to scholars of early Christianity. Egypt, Palestine, Syria and Asia Minor have been proffered as the most likely settings of origin (with the latter two favored especially in recent years). The educational scenes in IGT may provide helpful hints of the text's original setting. Paul Foster, however, in comparing the details of such scenes with depictions of education in literary sources, concludes that they offer no features suggestive of a particular setting of origin. However, comparison of such scenes with material depictions of ancient education may provide more geographical precision. A reexamination of the text's educational scenes vis-à-vis material-cultural evidence suggests that Egypt should be reconsidered as a viable setting of origin for IGT.